Educating a Moderate Generation: The Role of Non-Religious Teachers in Instilling the Values of Religious Moderation at SMPN 1 Rengasdengklok - Devi Hidayat; Muhamad Parhan (Electronic Journal of Education, Social Economics and Technology, 2025)
This article explores the strategic role of non-religious subject teachers in promoting religious moderation values at SMPN 1 Rengasdengklok, a school with students from diverse religious and cultural backgrounds. Using a qualitative approach and case study method, the study investigates how these teachers integrate core values of moderation national commitment, tolerance, anti-violence, and acceptance of local culture into general subject instruction. Data were collected through interviews, observations, and documentation, and analysed descriptively. The findings reveal that non-religious subject teachers successfully foster an inclusive and harmonious learning environment through contextual approaches, collaborative learning, and integration of local and national values. As a result, students show increased tolerance, a stronger sense of nationalism, and improved dialogical thinking. However, challenges remain, such as student intolerance, social media influence, and limited family support. Therefore, collaboration among schools, families, and communities, along with enhanced digital literacy and experiential learning, is essential to sustaining religious moderation practices. This study underscores the vital role of non-religious teachers as agents of moderation in shaping inclusive, peaceful, and patriotic student character.